Analysis of Organizational Structure Changes in the Rupiah Money Management Implementation Unit at the Representative Office of Bank Indonesia - Humairoh, Kirana; Kadiyono, Anissa Lestari (Psikostudia : Jurnal Psikologi, 2024)
Technological and economic developments in Indonesia have made Bank Indonesia continue to adjust, one of which is in the form of changes to the organizational structure carried out on the Payment System and Rupiah Management Team at the Representative Office of Bank Indonesia Province X. This study aims to see the effectiveness of these changes by providing an overview of the process of change in qualitative descriptive using the Star Model approach which consists of five aspects, namely strategy, structure, process, rewards, and people. Data collection was carried out using interviews and observations of informants who had been selected based on the purposive sampling method to 3 (three) employees of the Rupiah Money Management Division at the Bank Indonesia Representative Office Province X with different positions, namely cash administration assistant, cash administration senior executive, and an assistant supervisor. Furthermore, the data is analyzed by reviewing all available data sources until a synthesis is produced and a working hypothesis is developed. The results of the study indicate that the implementation of changes has considered policies in each category of the Star Model.Perkembangan teknologi dan ekonomi di Indonesia membuat Bank Indonesia terus melakukan penyesuaian, salah satunya adalah dalam bentuk perubahan struktur organisasi yang dilakukan pada Tim Pengelolaan Uang Rupiah di Kantor Perwakilan Bank Indonesia Provinsi X. Penelitian ini bertujuan untuk melihat efektivitas perubahan tersebut dengan memberikan gambaran proses perubahan secara deskriptif kualitatif dengan menggunakan pendekatan Star Model yang terdiri dari lima aspek, yaitu strategy, structure, process, rewards, dan people. Pengumpulan data dilakukan menggunakan metode wawancara dan observasi terhadap informan yang telah dipilih berdasarkan metode purposive sampling kepada 3 (Tiga) pegawai Divisi Pengelolaan Uang Rupiah Kantor Perwakilan Bank Indonesia Provinsi X dengan jabatan yang berbeda-beda, yaitu asisten administrasi perkasan, pelaksana senior administrasi perkasan, dan asisten penyelia perkasan. Selanjutnya data dianalisis sesuai dengan menelaah seluruh sumber data yang ada hingga kemudian dihasilkan sintesisasi dan menyusun hipotesis kerja. Hasil penelitian menunjukkan bahwa implementasi perubahan telah mempertimbangkan kebijakan dalam setiap kategori pada Star Model.